ALUMİNUM SECTOR, FOREİGN TRADE İN THE WORLD AND İN TURKEY, TURKEY'S COMPETİTİVENESS (Third Sector Social Economic Review, 2022)
In the study, examining the production and foreign trade of the aluminum industry in the world and in Turkey, the international competitiveness of Turkey's aluminum products between the years 2011-2020 was calculated using the ""Revealed Comparative Advantages"" (RCA) method. World aluminum demand was 65.3 million tons in 2020. China accounts for 57.20% of global primary aluminum production. While China has the largest share of global demand with 56.5%, it is followed by Europe; 13.8%, Asia (excluding China) ; 12.3% followed. North America; 10.0% Latin America; 1.9% and other countries; It has a share of 5.5%.World aluminum exports in the period of 2011-2020 varied between 155 billion dollars and 192 billion dollars. Total exports in 2020 amounted to 165,7 billion dollars. While China took the first place with an export of 24.6 billion dollars, the second Germany realized 14.78 billion dollars and the third USA realized 9.39 billion dollars. Turkey ranked 16th with 3.06 billion dollars of exports.Turkey's exports, which were 321 million dollars in 2004, increased continuously and reached 5.17 billion dollars in 2021. In 2021, 6,592 billion dollars of imports were made, and a foreign trade deficit of -1,418 billion dollars was given in the aluminum sector.Competitiveness of Turkey in Aluminum and Aluminum products;GTIP; It is seen in the product numbered 7601, 7602, 7603, 7605 that Turkey does not have a competitive power in this product.GTIP; It is on the border that Turkey has no competitive power in the product numbered 7606 and 7608.GTIP; It is seen that Turkey has competitive power in the product numbered 7604, 7607, 7609, 7610, 7611, 7612, 7613, 7614, 7615 and 7616.
Keywords: Aluminum Industry; Aluminum Foreign Trade; Competitiveness; Turkey's Foreign Trade; Revealed Comparative Advantages